HUBUNGAN ANTARA PENGGUNAAN DOSIS DENGAN RESIDU INSEKTISIDA SIDAZINON PADA KACANG PANJANG (VIGNA SINENSIS) DI DESA TUNJUK SELATAN, KECAMATAN TABANAN, KABUPATEN TABANAN - I Gusti Ayu Lani Triani (Bumi Lestari Journal of Environment, 2010)
This research was conducted in order to know relationship between dosage use with residue of the sidazinon insecticide in long bean that has been produced at Tunjuk Selatan village, Tabanan district, Tabanan regency. The determination of the sample of the farmer of long bean was done in proportional and purposive sampling. The sample was taken in Tabanan district, in Tabanan Regency. For the selection of village, search by 10 % from amount village exist, so five of the farmer of long bean were obtained in Tabanan district. The finding shows that residue of the sidazinon insecticide in long bean has enough strong relationship with dosage use, showed with value R : 0,707. With coefficient determination (R2) as 0,499; it mean 49,90 % residue insecticide come from dosege use of the sidazinon insecticide, while 50,1 % come from another factor. Dosage use of the sidazinon insecticide influenced at residue in long bean was significant with standard 5 %.